Glutamine Transport and Mitochondrial Metabolism in Cancer Cell Growth - Scalise, Mariafrancesca; Pochini, Lorena; Galluccio, Michele; Console, Lara; Indiveri, Cesare (Frontiers in Oncology, 2017)
The concept that cancer is a metabolic disease is now well acknowledged: many cancer cell types rely mostly on glucose and some amino acids, especially glutamine for energy supply. These findings were corroborated by over-expression of plasma membrane nutrient transporters, such as the glucose transporters GLUTs and some amino acid transporters such as ASCT2, LAT1 and ATB0,+, which became promising targets for pharmacological intervention. On the basis of their sodium dependent transport modes, ASCT2 and ATB0+ have the capacity to sustain glutamine need of cancer cells; while LAT1, that is sodium independent will have the role of providing cancer cells with some amino acids with plausible signaling roles. According to the metabolic reprogramming of many types of cancer cells, glucose is mainly catabolized by aerobic glycolysis in tumors, while the fate of Glutamine is completed at mitochondrial level where the enzyme Glutaminase converts Glutamine to Glutamate. Glutamine rewiring in cancer cells is heterogeneous. For example, Glutamate is converted to -Ketoglutarate giving rise to a truncated form of Krebs cycle. This reprogrammed pathway leads to the production of ATP mainly at substrate level and regeneration of reducing equivalents needed for cells growth, redox balance and metabolic energy. Few studies on hypothetical mitochondrial transporter for Glutamine are reported and indirect evidences suggested its presence. Pharmacological compounds able to inhibit Glutamine metabolism may represent novel drugs for cancer treatments. Interestingly, well acknowledged targets for drugs are the Glutamine transporters of plasma membrane and the key enzyme Glutaminase.